Prospective Study using Standardized Methodology for Antimicrobial Susceptibility of Gram-positive Cocci Isolated from the Puerto Rico Medical Center - Rodríguez, Jorge L.; Vázquez, Guillermo J.; Bermúdez, Myriam; De Orbeta, Jessica; García, Yaira; Rivera, Yisel; Robledo, Iraida E. (Puerto Rico Health Sciences Journal, 2012)
see manuscript